Uterus bicornis unicollis with multiple lieomyomas - Bafna, Barkha; Bafna, Amit; Bafna, Ashalata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Uterine anomalies are congenital malformations caused by fusion or resorption defects during embryogenesis. Uterus bicornis unicollis (bicornuate uterus) is a rare condition which results from incomplete fusion of uterovaginal horns at the level of the fundus. Here we report a case of a 30 year old (P2L0) female, with uterus bicornis unicollis with multiple lieomyomas (fibroids). The patient underwent hysterectomy with adnexa removal. The specimen showed multiple lieomyomas with hyaline degeneration.